2015
DOI: 10.3797/scipharm.1506-04
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Synthesis of N-(Arylalkyl)-1-R-4-hydroxy-2,2-dioxo-1,2-dihydro-2λ6,1-benzothiazine- 3-carboxamides as Promising Analgesics of a New Chemical Class

Abstract: A new, effective preparative method has been proposed and the synthesis of a series of N-(arylalkyl)-1-R-4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-car-boxamides has been carried out. It has been shown that amidation of alkyl 1-R-4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylates with arylalkyl-amines in boiling xylene proceeds with good yield and purity to the corresponding N-(arylalkyl)-amides. However, the presence of water in the reaction mixture has been shown to cause the formation of specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Melting points were determined in a capillary using a Stuart SMP10 digital melting point apparatus (Bibby Scientific Limited, Stone, UK). The starting N- benzyl-4-hydroxy-1-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothia-zine-3-carboxamide ( 1 ) and its pseudo-enantiomeric forms A and B were prepared by our previously described procedures [14] and [13] respectively. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting points were determined in a capillary using a Stuart SMP10 digital melting point apparatus (Bibby Scientific Limited, Stone, UK). The starting N- benzyl-4-hydroxy-1-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothia-zine-3-carboxamide ( 1 ) and its pseudo-enantiomeric forms A and B were prepared by our previously described procedures [14] and [13] respectively. …”
Section: Methodsmentioning
confidence: 99%
“…That is how we have recently registered the first example of conformational polymorphism not known before [13]. While studying N- benzyl-4-hydroxy-1-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxamide ( 1 ) crystal modifications described before and producing a high analgesic effect [14], it was found that this compound could form two pseudo-enantiomeric forms A and B , which are mirror images of each other (Figure 1). This fact seems interesting as there is no stereogenic atom in the original molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The analgesic activities of the synthesized 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxanilides 2а – l were studied compared to piroxicam (Jenapharm, Jena, Germany) and meloxicam (Boehringer Ingelheim, Ingelheim am Rhein, Germany), two structurally similar compounds, on the model of the thermal tail-flick procedure in white rats (tail immersion test) [ 28 ]. The conditions of our pharmacological experiments were previously described in detail [ 21 ]. The test compounds and the reference drugs were administered orally in a screening dose of 20 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, halogen-substituted benzene cores have a positive effect on the analgesic properties of compounds of different chemical classes as evidenced by their presence in the structure of many drugs of this pharmacological group ( Figure 2 ) [ 18 ]. Finally, the high analgesic activity is characteristic for 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxamides with different substituents in the terminal amide fragment, including hetaryl [ 15 , 16 , 19 , 20 ], aryl alkyl amide [ 21 ], and anilide [ 22 , 23 , 24 , 25 ] ones.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting objects of study in this respect are derivatives of 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylic acids. Their lower alkyl esters [ 11 , 12 ] and especially hetaryl- [ 13 , 14 , 15 , 16 ], aryl- [ 17 , 18 ] and benzyl- [ 19 ] amides in experiments on animals showed a high level of analgesic properties significantly exceeding the activity of structurally related drugs of oxicam series (meloxicam and piroxicam) in the same dose.…”
Section: Introductionmentioning
confidence: 99%